Avaliação da universalidade de primers de marcadores moleculares para aplicação na classe Chlorophyceae (Chlorophyta) - Vieira, Helena Henriques (2014)
The polifasic taxonomy approach became indispensable in classification of living beings, especially microorganisms, such as Chlorophyceae. This class is compound of very distinct organisms most microscopic, unicellular, colonials, filamentous, and the classification and identification is many times hampered due the lack of structures observable that helps the discrimination. Some habits, reproduction, the occurrence of cryptic species are some factors that can lead to forms that make difficult the taxonomy of these organisms. Besides the traditional morphology, the molecular biology allows a robust concerning the classification of the studied organism. Associated to a better classification, the search for faster and more practical methods of identification, as DNA Barcode, became intensified and many molecular markers are available in literature to be tested. For some groups of animals, brown algae, red algae and diatoms the marker COXI is considered an official DNA Barcode. However other groups, as Chlorophycea, are under constant investigation, due the fact that molecular marker that can be used satisfactory as DNA Barcode have not been found yet. Plastid markers as tufA, rbcL and nuclear as ITS are some of the most proposed to be applied in green algae, often combined with each other or other markers. However, for act as a molecular marker, it is necessary to be amplified by primers broadly applied. The present study has tested primers for tufA, ITS and rbcL marker, available in literature and already in use in other groups, looking for universality in Chlorophyceae. We also tested proposed universal primers for Chlorophyta (UCP4). Moreover, preliminary analyses have been performed for application of the markers as barcode in the class. The primers used for tufA marker showed universality in Chlorophycea amplifying for all 22 strains tested and sequencing have failed only for Oedogonium strain. From the rbcL marker, the primer pair GrbcL has amplified 12 and sequenced 7 of 22 strains and rbcLFP which one the reverse primer was designed in this study amplified and sequenced 16 lineages. Primers from the ITS marker amplified only 5 lineages and UCP4 primers have not amplified any strain. Beside the universality found for tufA primers, Analysis with the obtained sequences showed that the tufA gene is a promising molecular marker to be applied in Chlorophyceae.